Lactate Dehydrogenase as a Potential Therapeutic Drug Target to Control Babesia bigemina - He, Lan; Bastos, Reginaldo G.; Yu, Long; Laughery, Jacob M.; Suarez, Carlos E. (Frontiers in Cellular and Infection Microbiology, 2022)
Babesia bigemina is a tick-borne apicomplexan haemoprotozoan responsible for bovine babesiosis. Current drugs used for bovine babesiosis treatment have several drawbacks, including toxicity, lack of effectiveness to clear the parasite, and the potential to develop resistance. Identifying compounds that target essential and unique parasite metabolic pathways is a rational approach toward finding alternative drug treatments. Based on genome sequence and transcriptomics analysis, it can be inferred that anaerobic glycolysis is the dominant ATP supply for Babesia, and lactate dehydrogenase (LDH) is one of the essential enzymes in this pathway. Furthermore, Babesia LDH sequence is distinct from its bovine homologue, and thus a potential chemotherapeutic target that would result in decreasing the ATP supply to the parasite, but not to the host. Gossypol is a known efficient specific inhibitor of LDH in the sensu stricto Babesia bovis and the sensu lato Babesia microti, among other related parasites, but no such data is currently available in the sensu stricto Babesia bigemina parasites. Hereby we show that the LDH amino acid sequence is highly conserved among sensu stricto, but not in sensu lato Babesia spp. Predictive structural analysis of B. bigemina LDH showed conservation of key amino acids involved in the binding to gossypol compared to B. bovis. Gossypol has a significant (P < 0.0001) inhibitory effect on the in vitro growth of B. bigemina, with IC50 of 43.97 mM after 72 h of treatment. The maximum IC (IC98) was observed at 60 mM gossypol. However, significant effect on the viability of cattle PBMC was observed when the cells were cultured with 60 mM (IC98) gossypol compared with DMSO-exposed control cells. Interestingly, B. bigemina cultured at 3% oxygen express significant higher levels of LDH and are more resistant to gossypol than parasites maintained at ambient conditions containing 20% oxygen. Altogether, the results suggest the potential of gossypol as an effective drug against B. bigemina infection, but the risk of host toxicity at therapeutic doses should be further evaluated in in vivo studies.